Alpha heavy chain disease lacking secretory alpha chain, with cobblestone appearance of the small intestine and duodenal ulcer demonstrated by endoscopy. Issue 5 (May 1982) - Hibi, T; Asakura, H; Kobayashi, K; Munakata, Y; Kano, S; Tsuchiya, M; Teramoto, T; Uematsu, Y
Abstract : Ultrastructural and immunohistochemical studies of the small intestine are described in a Japanese patient with alpha heavy chain disease who had a history of colonic ulcers. Endoscopic examinations revealed multiple gastric erosion, duodenal ulcer, and a thickened, cobblestone-like pattern composed of small nodules in the duodenum and jejunum, which was similar in appearance to Crohn's disease. An electron microscopic study showed that the numerous, infiltrated cells in the jejunal lamina propria were matured plasma cells with atypical structure of the organelles. These plasma cells had alpha heavy chain protein devoid of light chain. Although secretory component was demonstrated normally in the epithelial cells by immunofluorescent methods, no association of this component with alpha heavy chain protein could be observed in any of the plasma and epithelial cells of this case. These facts suggest the absence of secretory alpha chain or secretory IgA, and a deficiency of the mucosal secretory immune system in this patient.